Abundance and biomass of macrobenthic organisms collected from grab and corer samples taken during five expeditions to Eurasian-Arctic seas between 1993 and 1995 - Boris I Sirenko; Jennifer Dannheim; Miriam Lea Sarah Hansen; Dieter Piepenburg (PANGAEA, 2024)
This dataset is a component of the PAN-Arctic data collection of benthic BIOtas (PANABIO) and has been collated during the Census of Marine Life project Arctic Ocean Diversity (ArcOD; http://www.arcodiv.org/). It contains a total of 3,240 abundance and wet biomass records of 686 macrobenthic taxa (species to family level) identified in 148 samples taken by means of two grabs and a box corer at 148 stations located in several Eurasian-Arctic seas (Kara, Laptev, East Siberian Seas) at water depths of 7–3,827 m during five cruises between 1993 and 1995. The dataset is also available in a PostgreSQL-based data warehouse that can be accessed and queried through an open-access frontend web service at https://critterbase.awi.de/panabio.
In: Piepenburg, Dieter; Brey, Thomas; Teschke, Katharina; Dannheim, Jennifer; Kloss, Paul; Hansen, Miriam Lea Sarah; Kraan, Casper (2023): PANABIO: A point-referenced pan-Arctic data collection of benthic biotas [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.963640